Pengaruh Struktur Modal Terhadap Kinerja Keuangan Perusahaan Consumer Goods di BEI - Syarifah Aini Ritonga; Ihsan Effendi; Ahmad Prayudi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This study aims to determine the effect of Debt to Equity Ratio (DER) and Debt to Equity Ratio (DAR) to Return On Assets (ROA) in Consumer Goods companies Sub Sector of Cigarette Listed on BEI in the period 2013- 2017. The research method used is an associative quantitative method. This research uses multiple linear regression analysis technique with Eviews 8.00. Population in this research is Consumer Goods company of Cigarette sub sector listed in BEI period 2013-2017. Sampling technique in this research use quota sampling. Based on the results of the study can be concluded that (1) DER has negative effect and hasn’t a significant effect on ROA. (2) DAR has a positive and significant effect on ROA. (4) DER and DAR simultaneously have a significant effect on ROA.